Characteristics of beef cattle farming in SPR and Non-SPR groups in Bomberay District, Fakfak Regency, West Papua Province Indonesia - Nuraini Werfete; Mohamad Jen Wajo; Lukas Y Sonbait; Diana Sawen; Sientje D. Rumetor (Fakultas Peternakan Universitas Papua, 2026)
The beef cattle farming sector plays a critical role in supporting Indonesia's food security and rural livelihoods. This study aims to compare the characteristics of beef cattle farming between groups of farmers participating in the “Sekolah Peternakan Rakyat” (SPR, or People's Livestock School) and non-SPR farmers in Bomberay District, Fakfak Regency, Indonesia. Using a descriptive case study approach, 14 farmers (7 from SPR and 7 from non-SPR) were selected. Data were collected through structured interviews and analyzed using Fisher's Exact Test. Key variables assessed included farmer demographics, management practices, feed systems, breeding methods, waste handling, and farm productivity. Results showed significant associations between SPR participation and knowledge of feed processing (p=0.0016), ownership of forage gardens (p=0.041), and type of housing system (p=0.024). SPR farmers exhibited more advanced practices, particularly in technical knowledge and collective farm management. The study highlights the importance of structured farmer education programs such as SPR in improving livestock productivity and rural empowerment.